Taxonomic notes on two species of bush katydids (Orthoptera: Tettigoniidae: Phaneropterinae) from Bukit Fraser, Malay Peninsula - Tan, Ming Kai; Kamaruddin, Khairul Nizam (Zootaxa, 2013)
Material based on a taxonomic collection in Bukit Fraser, Pahang of Malay Peninsula enables the review of two genera of bush katydid (Phaneropterinae). The female of Elimaea (Rhaebelimaea) pseudochloris Ingrisch, 1998 is described and recorded for the first time outside its type locality, Thailand. One new species of Pseudopsyra from Bukit Fraser is described: Pseudopsyra bispina sp. n.